1976
DOI: 10.1002/pssb.2220740249
|View full text |Cite
|
Sign up to set email alerts
|

Note on the Mermin‐Wagner Theorem

Abstract: Note on the Mermin-Wagner Theoreni BY s. KRZEMII~SKI Mermin and Wagner (1) have rigorously shown that there can be no spontaneous magnetization in the one-and two-dimensional isotropic Heisenberg ferromagnet , and no spontaneous sublattice magnetization in the one-and two-dimensional isotropic two-sublattice antiferromagnet, at any finite temperature. Their proof was extended to a lattice which has an arbitrary number of magnetic sublattices (2), (3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Thorpe [28] considers the case of ferromagnetism in phenomenological models with double and higher-order exchange terms; similar results were obtained in the multi-sublattice case by Krzemiński. [29] These methods differ from others in that the Hamiltonian is written as a series expansion in terms of spin spherical harmonics, thus offering a more systematic way of evaluating the Bogoliubov inequality using the defining properties of spin spherical harmonics. A closely related proof, using spherical tensor operators, has been put forward for the problem of ordering in quadrupolar systems of restricted dimensionality.…”
Section: Spin Systemsmentioning
confidence: 99%
“…Thorpe [28] considers the case of ferromagnetism in phenomenological models with double and higher-order exchange terms; similar results were obtained in the multi-sublattice case by Krzemiński. [29] These methods differ from others in that the Hamiltonian is written as a series expansion in terms of spin spherical harmonics, thus offering a more systematic way of evaluating the Bogoliubov inequality using the defining properties of spin spherical harmonics. A closely related proof, using spherical tensor operators, has been put forward for the problem of ordering in quadrupolar systems of restricted dimensionality.…”
Section: Spin Systemsmentioning
confidence: 99%
“…This proof was obtained by using the Bogoliubov's inequality and developing a mathematical approach based on writing terms of the spin equivalent of the spherical harmonics. A few years later, Krzemiński used the same mathematical method and came to similar conclusions demonstrating the absence of long-range order also in multi-sublattice systems [25]. The absence of off-diagonal longrange order and of long-range order was demonstrated in 2D ferromagnetic lattices described via the Heisenberg model by Suzuki [26] who also showed that, in systems with higher spins leading to a different definition of order parameter, off-diagonal long-range order can exist and the order parameter can remain finite.…”
Section: Introductionmentioning
confidence: 75%
“…Finally, the absence of spontaneous breaking of continuous and internal symmetries, of crystalline ordering in 2D systems and uniqueness of equilibrium states was proved by Frölich and Pfister [27] according to a unified approach based on Araki's relative entropy concept. However, for the systems studied in [24][25][26][27], the analysis was mainly mathematical and the physical effects of the biquadratic exchange interaction were not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Since then various more precise and more general versions have been considered (see Refs. 300,[306][307][308][309][310][311] ). These considerations of symmetry broken systems are important in order to establish whether or not long-range order is possible in various concrete situation.…”
Section: Bogoliubov's Inequality and The Mermin-wagner Theoremmentioning
confidence: 99%